Pengaruh Kematangan Emosi Terhadap Kesiapan Pernikahan Siswa Tingkat Akhir Poltekkes Kemenkes Surabaya: The Effect of Emotional Maturity on The Marriage Readiness of Final Year Students of the Ministry of Health Polytechnic of The Ministry of Health Surabaya - Shela Putri; Tatarini Ika Pipitcahyani; Triana Septianti Purwanto; Esyuananik (Jurusan Kebidanan Politeknik Kesehatan Kemenkes Surabaya, 2025)
Introduction : The emotional maturity is crucial in maritial life as it enables individuals to approach marriage with a mature mindset and handle it effectively. Divorce is a common issue within households, emphasizing the significance of emotional readiness and maturity in forming a happy family. Both elements are pivotal in preparing for marriage, indicating readiness. A mature individual, having met these criteria, can be deemed ready for marriage. This study aims to investigate the influence of emotional maturity on marriage readiness among senior female students at the Surabaya Health Polytechnic. Methods : The research design employed an analytical survey with a cross-sectional design, involved 180 female students selected through proportionate stratified random sampling at the Surabaya Health Polytechnic. The independent variable is emotional maturity, on the other hand the dependent variable is marriage readiness. Primary data collection are conducted through the Emotional Maturity Scale and Marriage Readiness Scale’s questionnaires. Result : The analysis using chi-square, reveals a significant association between high levels of emotional maturity and marriage readiness, with a p-value of 0.04. High emotional maturity have significantly influences marriage readiness among senior female students at the Surabaya Health Polytechnic Disscusion : It is hoped that all female students recognize the importance of emotional maturity, particularly in preparing for marriage, thereby preventing divorce rates.